Alternative Measures of Price Inflation and the Perception of Real Income in Germany - Karl-Friedrich Israel; Gunther Schnabl (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Since the 1980s inflationary pressures seem to materialize overproportionately outside of the sectors of consumer goods and services. We combine the Harmonized Index of Consumer Prices with indices for asset prices, such as stocks and real estate, as well as the costs of public goods to develop alternative inflation measures in Germany since the introduction of the euro. Real economic growth as well as median wage developments are reexamined in light of the alternative inflation estimates. Both turn out to be negative over the past decade in the most pessimistic scenarios.
Keywords: E31; E52; E58; O11; 330; inflation; harmonized index of consumer prices; hidden inflation; assets prices; costs of public goods; inflation targeting; monetary policy; real wages; real economic growth; Germany